Library Collection Management: Catalogization And Classification In Madrasah Libraries - Merrina Ulfa; Muhammad Aryo Ramadhan; Instiyawati Hakim (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
This study aims to examine the implementation of cataloging and classification of El-Hayaah library collections at State Islamic Senior High School (MAN) 1 Pekanbaru and analyze its role in supporting effective and efficient library management. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The results show that cataloging and classification are carried out manually and digitally using the Dewey Decimal Classification (DDC) system and barcode -based applications. This process simplifies collection management, borrowing, and returning books. Collection evaluation and maintenance are carried out twice a year, with direct and indirect preservation strategies. In addition, increasing reading interest is carried out through scheduled class visits and thematic book classification. The study concludes that systematic collection management contributes significantly to supporting student literacy. It is recommended that libraries expand digitalization and librarian training to improve information technology-based services.